L’intérêt environnemental des ruines urbaines : la présence de l’anthropocène au-delà des patrimoines culturels et naturels - Nathanaël Wadbled (Territoire en Mouvement, 2022)
The presence of the ruins questions the very of heritage: they escape the tension between the artificial and the natural that structures it. They are not only the testimony of human actions, but also that of the action of nature on them. Heritage, however, institutionalizes the relationship between humans and non-humans in the articulation between cultural and natural heritages. There is therefore no category for an object such as ruin. However, it addresses environmental concerns in the context of ecological crises. The ruins then constitute a heritage of the anthropocene that testifies to the entanglement of humans and non-humans in a common environment. They are the material culture of an environment composed of humans and non-humans beyond the opposition between the artificial and the natural, a dark heritage of the failure of a totally artificial environment to maintain itself and a civic monument inspire the development of values intended to avoid ecological crises. Before describing the way in which visitors to the ruins apprehend this hybridity and the way in which institutions present it, a theoretical critique of the notion of heritage is necessary.